Multilayer Security System - Rahman, Jabel; Al-Amin, Mohammad; Saha, Surojit (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.